Sealing film, tab lead, and battery
Patent Information
- Application Number
- JP2025058582
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0007】 本発明によれば、開封すべき温度未満では十分高い水準の封止強度を維持し、かつ、開封すべき温度および内圧に達したときに速やかに開封させることが可能な、封止フィルム並びにこれを備えたタブリード及び電池を提供することができる。
Smart Images

Figure 2026165922000001_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a sealing film, a tab lead, and a battery.
Background Art
[0002] For pouch-type batteries equipped with a sealing film for tab leads (tab film), it has been proposed to release the internal gas by causing the tab film to unseal when the temperature inside the battery rises and the internal pressure increases due to gas generated inside the battery. (See, for example, Patent Documents 1 to 3)
Prior Art Documents
Patent Documents
[0003]
Patent Document 1
Patent Document 2
Patent Document 3
Summary of Invention
Problems to be Solved by the Invention
[0004] However, the conventionally proposed tab films with safety functions have a gentle change in sealing strength with temperature, and there are problems that the films do not unseal unless the inside of the battery reaches a considerably high pressure even when the temperature reaches the level at which unsealing should occur, or the sealing strength at normal operating temperatures is insufficient.
[0005] The present invention provides a sealing film, as well as a tab lead and a battery equipped with the same, which can maintain a sufficiently high level of sealing strength below the temperature at which unsealing should occur, and can be promptly unsealed when the temperature and internal pressure for unsealing are reached.
Means for Solving the Problems
[0006] The present invention includes the following aspects.[1] A sealing film comprising, in this order, a first adhesive layer, a core layer, and a second adhesive layer, comprising an acid-modified polyolefin resin, and a measurement method comprising the following steps (1), (2), (3) and (4) in this order: (1) Two sealing films with a length of 10 mm are stacked on both sides of a nickel-plated copper plate (CuNi plate) with a rectangular shape of 40 mm width and 52.5 mm length and a copper plate portion thickness of 200 μm, such that the ends of the CuNi plate in the longitudinal direction are not covered by the sealing film, the ends of the sealing film are in contact with each other in the width direction of the CuNi plate, and the first adhesive layer is in contact with the CuNi plate within the width direction of the CuNi plate, in the order of sealing film-CuNi plate-sealing film, and a pair of first metal heating parts are in contact with the CuNi plate facing each other in the longitudinal direction, and polytetrafluoroethylene is in contact with the sealing film. (1) Using a heat sealing machine equipped with a pair of film heating units that contact via tape, and a pair of second metal heating units that contact the CuNi plate facing each other, heat sealing is performed for 25 seconds under the conditions that the temperatures of the first and second metal heating units are 180°C and the temperature of the film heating unit is 150°C, thereby bonding the sealing film to the CuNi plate, and obtaining a first composite having a layer structure of sealing film-CuNi plate-sealing film; (2) An aluminum laminate film having a layer structure of polyethylene terephthalate layer / polycaprolactam layer / aluminum foil / polypropylene layer with a melting point of 140°C is superimposed on the sealing film portions on both sides of the first composite such that the polypropylene layer contacts the second adhesive layer of the sealing film, and heat sealing is performed at 190°C using a sealing bar with a heat sealing width of 4.5 mm along the length direction.(1) A step of obtaining a second composite having a layer structure of aluminum laminate film - sealing film - CuNi plate - sealing film - aluminum laminate film, by heat sealing for 5 seconds, the thickness of which is reduced by 5% from the sum of the thickness of the aluminum laminate film, the thickness of the sealing film, and the thickness of the CuNi plate before heat sealing, and (2) a step of cutting the second composite in a direction transverse to the width direction of the sealing film to cut out a third composite with a width of 15 mm, (3) fixing the CuNi plate of the third composite and heating one of the aluminum laminate films at a temperature of 23°C, 80°C, 110°C, or 130°C. A sealing film in which the peel strength measured by a 180° peel test under the conditions of °C and a tensile speed of 50 mm / min satisfies the following relationships, where F23 is the peel strength at 23°C in step (4), F80 is the peel strength at 80°C in step (4), F110 is the peel strength at 110°C in step (4), and F130 is the peel strength at 130°C in step (4): F23 ≥ 80 N / 15 mm (I), F80 ≥ 0.30 × F23 (II), F110 ≥ 0.120 × F23 (III), F130 ≤ 0.050 × F23 (IV). [2] The sealing film according to [1], wherein each layer of the layer group, which includes at least one layer other than the core layer, comprises a crystalline polyolefin resin which contains olefin monomer units having 3 or more carbon atoms and may be acid-modified, and a polyolefin elastomer which contains more than 50 mol% of olefin monomer units having 3 or more carbon atoms and more than 0 mol% but less than 50 mol% of ethylene monomer units. [3] The sealing film according to [2], wherein the melting point of the crystalline polyolefin resin contained in each layer of the layer group is 130°C or lower. [4] The sealing film according to [2], wherein each layer of the layer group comprises 35 to 88% by mass of the crystalline polyolefin resin and 12 to 65% by mass of the polyolefin elastomer. [5] The sealing film according to any one of [1] to [4], wherein the second adhesive layer comprises a crystalline polyolefin resin which contains olefin monomer units having 3 or more carbon atoms and may be acid-modified, and a polyolefin elastomer which contains more than 50 mol% of olefin monomer units having 3 or more carbon atoms and more than 0 mol% but less than 50 mol% of ethylene monomer units. [6] The sealing film according to [5], wherein the melting point of the crystalline polyolefin resin contained in the second adhesive layer is 130°C or less. [7] The sealing film according to [5] or [6], wherein the second adhesive layer comprises 35 to 88% by mass of the crystalline polyolefin resin and 12 to 65% by mass of the polyolefin elastomer. [8] The sealing film according to any one of [1] to [7], further comprising a first intermediate layer disposed between the first adhesive layer and the core layer, wherein the first intermediate layer comprises a crystalline polyolefin resin containing olefin monomer units having 3 or more carbon atoms and which may be acid-modified, and a polyolefin elastomer containing more than 50 mol% of olefin monomer units having 3 or more carbon atoms and more than 0 mol% but less than 50 mol% of ethylene monomer units. [9] The sealing film according to [8], wherein the melting point of the crystalline polyolefin resin contained in the first intermediate layer is 130°C or less.
[10] The sealing film according to [8] or [9], wherein the first intermediate layer comprises 35 to 88% by mass of the crystalline polyolefin resin and 12 to 65% by mass of the polyolefin elastomer.
[11] The sealing film according to any one of [1] to
[10] , further comprising a second intermediate layer disposed between the second adhesive layer and the core layer, wherein the second intermediate layer comprises a crystalline polyolefin resin which contains olefin monomer units having 3 or more carbon atoms and may be acid-modified, and a polyolefin elastomer which contains more than 50 mol% of olefin monomer units having 3 or more carbon atoms and more than 0 mol% but less than 50 mol% of ethylene monomer units.
[12] The sealing film according to
[11] , wherein the melting point of the crystalline polyolefin resin contained in the second intermediate layer is 130°C or lower.
[13] The sealing film according to
[11] or
[12] , wherein the second intermediate layer comprises 35 to 88% by mass of the crystalline polyolefin resin and 12 to 65% by mass of the polyolefin elastomer.
[14] The sealing film according to any one of [2] to
[13] , wherein the crystalline polyolefin resin is a crystalline polyolefin resin polymerized using a metallocene catalyst.
[15] The sealing film according to any one of [1] to
[14] , wherein the core layer comprises one or more resins selected from the group consisting of polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyphenylene sulfide (PPS), optionally acid-modified block polypropylene (PP-B), optionally acid-modified homopolypropylene (PP-H), and optionally acid-modified random polypropylene (PP-R) with a melting point of 140°C or higher.
[16] A tab lead comprising a metal terminal and a sealing film according to any one of [1] to
[15] bonded to the metal terminal.
[17] A battery comprising a battery enclosure, a power generation element housed in the battery enclosure, a positive electrode tab lead connected to the positive electrode of the power generation element, and a negative electrode tab lead connected to the negative electrode of the power generation element, wherein at least one of the positive electrode tab lead and the negative electrode tab lead is the tab lead described in
[16] . [Effects of the Invention]
[0007] According to the present invention, it is possible to provide a sealing film, a tab lead equipped with the same, and a battery that maintains a sufficiently high level of sealing strength below the temperature at which it should be opened, and can be quickly opened when the temperature and internal pressure at which it should be opened are reached. [Brief explanation of the drawing]
[0008] [Figure 1] This is a cross-sectional view showing a first example of the sealing film of the present invention. [Figure 2] It is a cross-sectional view showing a second example of the sealing film of the present invention. [Figure 3] It is a cross-sectional view showing a third example of the sealing film of the present invention. [Figure 4] It is an explanatory diagram showing step (1) of the peel strength measurement method. [Figure 5] It is an explanatory diagram showing step (2) of the peel strength measurement method. [Figure 6] It is an explanatory diagram showing step (3) of the peel strength measurement method. [Figure 7] It is an explanatory diagram showing step (4) of the peel strength measurement method. [Figure 8] It is a partially cutaway perspective view showing an example of a battery. [Figure 9] It is a plan view showing three pairs of heating units of a heat sealer. [Figure 10] It is a cross-sectional view taken along the X-X arrow in Figure 9. [Modes for Carrying Out the Invention]
[0009] Hereinafter, the present invention will be described based on preferred embodiments. The drawings are for conceptual illustration, and the dimensions, ratios, and the like of the components may differ from actual ones. Unless otherwise specified in the present specification or in the standards identified in the present specification, tests and measurements are performed in an atmosphere at 23°C and 1 atmosphere.
[0010] Figure 1 is a cross-sectional view showing a sealing film 10 of a first example. The sealing film 10 of the first example includes a first adhesive layer 11, a core layer 13, and a second adhesive layer 12, in this order.
[0011] Figure 2 is a cross-sectional view showing a sealing film 10A of a second example. The sealing film 10A of the second example further includes a first intermediate layer 14 disposed between the first adhesive layer 11 and the core layer 13.
[0012] Figure 3 is a cross-sectional view showing a sealing film 10B of a third example. The third sealing film 10B further comprises a second intermediate layer 15 positioned between the second adhesive layer 12 and the core layer 13. In the illustrated example, if the first adhesive layer 11 and the second adhesive layer 12 have the same composition, and the first intermediate layer 14 and the second intermediate layer 15 have the same composition, there is the advantage that it does not matter if the front and back are reversed. Although not specifically shown, a sealing film comprising the first adhesive layer 11 / core layer 13 / second intermediate layer 15 / second adhesive layer 12 is also conceivable.
[0013] In all of the sealing films 10, 10A, and 10B, the first adhesive layer 11 contains an acid-modified polyolefin resin. In the case of a sealing film that can be used with either side reversed, the first adhesive layer 11 and the second adhesive layer 12 contain an acid-modified polyolefin resin.
[0014] In each layer constituting the sealing film, examples of polyolefins include polypropylene, polyethylene, poly-1-butene, and polyisobutylene. The polyolefin may be a copolymer of two or more olefin monomers. Examples of olefin monomers include propylene, ethylene, 1-butene, isobutylene, and 1-hexene.
[0015] Polyolefins may be copolymers of propylene and other olefin monomers. Polyolefins may also be copolymers of ethylene and other olefins. Polyolefins containing ethylene as a comonomer may be random copolymers (random polyolefins) or block copolymers (block polyolefins).
[0016] Examples of acid-modified polyolefins include copolymers of olefin monomers and monomers having acidic groups, and graft polymers obtained by graft polymerization of polyolefins with monomers having acidic groups. In acid-modified polyolefins, monomer units having acidic groups may be included in the side chains or in the main chain. Examples of monomers having acidic groups include unsaturated carboxylic acids such as acrylic acid, methacrylic acid, fumaric acid, maleic acid, itaconic acid, and citraconic acid; and unsaturated carboxylic acid anhydrides such as maleic anhydride, itaconic anhydride, and citraconic anhydride.
[0017] Preferred examples of acid-modified polyolefins include maleic acid-modified polyolefins, maleic anhydride-modified polyolefins, and acrylic acid-modified polyolefins. Acid-modified polyolefins may contain ethylene as a comonomer. Acid-modified polyolefins containing ethylene as a comonomer may be acid-modified random polyolefins or acid-modified block polyolefins.
[0018] Each layer of the sealing film may further contain non-polymer additives along with the resin mentioned above. Examples of non-polymer additives include antioxidants and compatibilizers.
[0019] In this specification, "sealing film of this embodiment" also includes sealing films comprising a first adhesive layer 11 / core layer 13 / second intermediate layer 15 / second adhesive layer 12, although these are not specifically shown. That is, the presence or absence of the first intermediate layer 14 and the second intermediate layer 15 is independent and optional.
[0020] <Sealing film> The sealing film of this embodiment satisfies the relationship expressed in (I), (II), (III), and (IV) below, when measured by a measurement method comprising the following steps (1), (2), (3), and (4) in that order.
[0021] F23≧80N / 15mm ···(I) F80≧0.30×F23 ···(II) F110≧0.120×F23 ···(III) F130 ≤ 0.050 × F23 ···(IV)
[0022] In relational equations (I) to (IV), the peel strength at a temperature of 23°C in process (4) is defined as F23. The peel strength at a temperature of 80°C in process (4) is defined as F80. The peel strength at a temperature of 110°C in process (4) is defined as F110. The peel strength at a temperature of 130°C in process (4) is defined as F130.
[0023] F23 satisfies relation (I), providing sufficient sealing strength at room temperature. Normally, sealing strength decreases as the temperature rises, but F80 and F130 satisfy relation (II) and (III), respectively, allowing sufficient sealing strength to be maintained within the normal operating temperature range. Furthermore, F130 satisfies relation (IV), allowing the sealing strength to rapidly decrease when the temperature rises to the temperature at which it should be opened, enabling quick opening.
[0024] In conventional technology, sealing films that satisfy relational equations (I) to (III) do not satisfy relational equation (IV) because the decrease in sealing strength is gradual even at high temperatures, and sealing films that satisfy relational equation (IV) do not satisfy relational equations (II) or (III), especially relational equation (III), because the decrease in sealing strength with increasing temperature is rapid even in the normal operating temperature range. In contrast, the sealing film of this embodiment satisfies relational equations (I) to (IV), thereby maintaining a sufficiently high level of sealing strength below the temperature at which it should be opened, and allowing it to be opened quickly when the temperature and internal pressure at which it should be opened are reached.
[0025] Step (1), as shown in Figure 4, is a step in which the sealing film of this embodiment is heat-sealed to adhere to a CuNi plate to obtain a first composite 111 having a layer structure of sealing film-CuNi plate-sealing film. In the first composite 111, a predetermined CuNi plate is used as the test metal terminal 101. Furthermore, a fragment obtained from the sealing film of this embodiment can be used as the test sealing film 102.
[0026] The CuNi plate used as the test metal terminal 101 is a rectangular nickel-plated copper plate with a width (Wt) of 40 mm and a length (Lt) of 52.5 mm, and a copper plate portion thickness of 200 μm. For this CuNi plate, a copper plate with a thickness of 200 μm and a 2.5 μm Ni plating can be used. Here, the thickness of the Ni plating layer is the value per side, not the sum of both sides. The Ni plating may be pure Ni plating or Ni-P plating. Note that the same measurement results can be obtained by using, for example, a 200 μm thick aluminum plate as the test metal terminal 101 instead of the CuNi plate. This is because, when the peel strength of the sealing film of the present invention is measured by the measurement method comprising steps (1) to (4), peeling occurs in modes other than interfacial peeling between the first adhesive layer and the metal. This is because the first adhesive layer contains an acid-modified polyolefin, which forms a chemical bond with the metal surface on which the oxide film is formed, and because the area of the heat-sealed portion between the first adhesive layer 11 formed in step (1) and the test metal terminal 101 is larger than the area of the heat-sealed portion between the second adhesive layer 12 formed in step (2) and the aluminum laminate film. Since aluminum, like nickel, also forms an oxide film in the atmosphere, the same is true when an aluminum plate is used as the test metal terminal. Because the adhesion between the first adhesive layer 11 and the test metal terminal 101 is due to the formation of a chemical bond, the first adhesive layer 11 adheres firmly to the test metal terminal 101 even if the surface of the test metal terminal 101 is mirror-like (for example, the arithmetic mean height Sa of the surface is less than 0.05 μm). The surface roughness of the test metal terminal 101 may be, for example, 0.05 to 4 μm as the arithmetic mean height Sa defined in JIS B0681-2, and 0.2 to 25 μm as the maximum height Sz defined in JIS B0681-2. Surface roughness can be measured using a confocal laser microscope.
[0027] When two test sealing films 102 are stacked on both sides of the CuNi plate in the order of sealing film-CuNi plate-sealing film, the following conditions (1a), (1b), and (1c) are satisfied.
[0028] (1a) Both ends of the test metal terminal 101 (CuNi plate) in the longitudinal direction L are not covered by the test sealing film 102. (1b) In the width direction W of the test metal terminal 101 (CuNi plate), both ends of the test sealing film 102 are in contact with each other at the first adhesive layers 11. (1c) Within the width direction W of the test metal terminal 101 (CuNi plate), the first adhesive layer 11 of the test sealing film 102 is in contact with the CuNi plate.
[0029] The lengthwise dimension (Lf) of the test sealing film 102 is 10 mm. To satisfy (1b), the widthwise dimension Wf of the test sealing film 102 is sufficiently larger than the width Wt of the CuNi plate.
[0030] The first composite 111 is a composite having a layer structure of sealing film-CuNi plate-sealing film, formed by bonding a sealing film to a CuNi plate using a heat sealing machine equipped with three pairs of heating units. The heat sealing conditions are to set the temperature of the two pairs of metal heating units in contact with the CuNi plate to 180°C, the temperature of the one pair of film heating units in contact with the sealing film to 150°C, and to perform heat sealing for 25 seconds while applying pressure at 0.2 MPa.
[0031] Figure 9 is a plan view showing the three pairs of heating sections of the heat sealing machine in process (1), and Figure 10 is a cross-sectional view taken along the XX arrow in Figure 9. That is, Figure 9 is a plan view of one of each of the three pairs of heating sections of the heat sealing machine in process (1), viewed from the same direction as in Figure 4. In Figure 9, arrow L represents the length direction L in Figure 4, and arrow W represents the width direction W in Figure 4.
[0032] As shown in Figures 9 and 10, the three pairs of heating sections each consist of a pair of film heating sections Hf, Hf that face the sealing film and contact it via a polytetrafluoroethylene tape (not shown; hereinafter referred to as "PTFE tape"), a pair of first metal heating sections Hm1, Hm1 that face the CuNi plate and contact it, and a pair of second metal heating sections Hm2, Hm2 that face the CuNi plate and contact it. The film heating section Hf is positioned adjacent to the first metal heating section Hm1 and the second metal heating section Hm2 so as to be sandwiched between the first metal heating section Hm1 and the second metal heating section Hm2 in the longitudinal direction L.
[0033] The dimensions of the film heating section Hf are 15 mm in the length direction L and 90 mm in the width direction W. The dimensions of the first metal heating section Hm1 are 4 mm in the length direction L and 60 mm in the width direction W. The dimensions of the second metal heating section Hm2 are 7 mm in the length direction L and 60 mm in the width direction W. The distance between the film heating section Hf and the first metal heating section Hm1, and the distance between the film heating section Hf and the second metal heating section Hm2, can be set to a distance that allows sufficient heating of the area in contact with the sealing film 102 of the CuNi plate, and can be, for example, 1 to 2 mm in each case.
[0034] The surface of the film heating unit Hf that contacts the sealing film 102 is covered with PTFE tape to prevent the sealing film 102 from sticking to the film heating unit Hf. The film heating unit Hf contacts the sealing film 102 via the PTFE tape and heats the sealing film 102 via the PTFE tape. This prevents the film heating unit Hf from directly contacting the sealing film 102.
[0035] The PTFE tape comprises a PTFE film with a thickness of 0.05 mm and a silicone-based adhesive layer with a thickness of 0.04 mm provided on one side of the PTFE film, and is attached to the film heating section Hf by the silicone-based adhesive layer. Since the PTFE tape is very thin (thickness 0.09 mm), the temperature of the PTFE tape can be considered equal to the temperature of the film heating section Hf. As such a PTFE tape, for example, PTFE tape 5480 manufactured by 3M Company can be used.
[0036] Step (2), as shown in Figure 5, is the step of layering a predetermined aluminum laminate film 103 onto the first composite 111 described above to obtain a second composite 112 having a layer structure of aluminum laminate film - sealing film - CuNi plate - sealing film - aluminum laminate film.
[0037] The aluminum laminate film 103 has a layer structure consisting of a polyethylene terephthalate layer, a polycaprolactam (nylon-6) layer, aluminum foil, and a polypropylene layer with a melting point of 140°C. Of the aluminum laminate film 103, the polypropylene (PP) layer, which acts as a sealant, is superimposed on the sealing film portions on both sides of the first composite 111 so that it is in contact with the second adhesive layer 12 of the test sealing film 102.
[0038] The dimensions (heat seal width Lb) of the seal bar 104 in the longitudinal direction L are 4.5 mm. Using such a seal bar, a second composite 112 is obtained by heat sealing at a seal bar temperature of 190°C and a heating time of 3.5 seconds.
[0039] The second composite 112 after heat sealing (see Figure 6) includes a heat-sealed portion 105 with a length L dimension (Lh) of 4.5 mm. The heat-sealed width Lh of the heat-sealed portion 105 is approximately the same as the heat-sealed width Lb of the seal bar 104.
[0040] In the heat-sealed portion 105, the composite is 5% thicker than the total thickness of each layer before heat sealing. Here, the total thickness of each layer before heat sealing is the sum of twice the thickness of the aluminum laminate film 103, twice the thickness of the test sealing film 102, and the thickness of the test metal terminal 101 (CuNi plate).
[0041] Step (3), as shown in Figure 6, is the step of cutting the second composite 112 along a predetermined cutting line 106 to cut out a third composite 113 with a width (Ws) of 15 mm. The multiple cutting lines 106 are set parallel to each other in a direction that crosses the test sealing film 102 in the width direction W.
[0042] Step (4) is a step in which the peel strength is measured using the third composite 113, as shown in Figure 7. As described above, the third composite 113 is a composite having a layer structure in the thickness direction T of aluminum laminate film - sealing film - CuNi plate - sealing film - aluminum laminate film.
[0043] The method for measuring the peel strength is to fix the test metal terminal 101 (CuNi plate) of the third composite 113 and perform a 180° peel test on one of the aluminum laminate films 103 under the condition of a tensile speed of 50 mm / min. Either of the two aluminum laminate films 103 may be used for the peel test. The 180° peel test can be performed in accordance with JIS Z0237 (Method 1).
[0044] The measurement temperature for peel strength is one of 23°C, 80°C, 110°C, or 130°C. Each time peel strength is measured at a different temperature, a third composite 113 with the same specifications but different individual components is fabricated. Alternatively, when measuring peel strength at the same temperature, a third composite 113 with the same specifications but different individual components may be fabricated, and the average of the measured peel strength values may be calculated.
[0045] In the sealing film of this embodiment, it is preferable that one or more layers other than the core layer 13 include a crystalline polyolefin resin which contains olefin monomer units having 3 or more carbon atoms and may be acid-modified, and a polyolefin elastomer which contains more than 50 mol% of olefin monomer units having 3 or more carbon atoms and more than 0 mol% but less than 50 mol% of ethylene monomer units. In one preferred embodiment, one or more layers other than the first adhesive layer 11 and the core layer 13 may include a crystalline polyolefin resin which contains olefin monomer units having 3 or more carbon atoms and may be acid-modified, and a polyolefin elastomer which contains more than 50 mol% of olefin monomer units having 3 or more carbon atoms and more than 0 mol% but less than 50 mol% of ethylene monomer units. In this case, the first adhesive layer 11 may further include a crystalline polyolefin resin which contains olefin monomer units having 3 or more carbon atoms and may be acid-modified, and a polyolefin elastomer which contains more than 50 mol% of olefin monomer units having 3 or more carbon atoms and more than 0 mol% but less than 50 mol% of ethylene monomer units.
[0046] In the following description, regardless of whether the sealing film of this embodiment includes a first intermediate layer 14 or a second intermediate layer 15, the group of layers consisting of the first adhesive layer 11, the second adhesive layer 12, the first intermediate layer 14, and the second intermediate layer 15 may be referred to as the "first group of layers," and the group of layers consisting of the second adhesive layer 12, the first intermediate layer 14, and the second intermediate layer 15 may be referred to as the "second group of layers." In the sealing film of this embodiment, it is preferable that at least one layer selected from the first group of layers includes the crystalline polyolefin resin and the polyolefin-based elastomer. In one preferred embodiment, at least one layer selected from the second group of layers may include the crystalline polyolefin resin and the polyolefin-based elastomer. In this case, the first adhesive layer 11 may further include the crystalline polyolefin resin and the polyolefin-based elastomer. However, if the first adhesive layer 11 contains the crystalline polyolefin resin, the first adhesive layer 11 contains acid-modified crystalline polyolefin as all or part of the crystalline polyolefin resin.
[0047] In this specification, when a particular layer is said to contain two or more components, it means that the layer is a single layer and is composed of a composition (mixture) containing those two or more components. Furthermore, a composition containing the crystalline polyolefin resin and the polyolefin-based elastomer may be referred to as a "specific composition." The crystalline polyolefin resin contained in the specific composition may be one or more types. Similarly, the polyolefin-based elastomer contained in the specific composition may be one or more types. By having one or more layers from the first or second layer group composed of a specific composition, it becomes easier to provide sufficient sealing strength in the normal operating temperature range while rapidly reducing the sealing strength at high temperatures.
[0048] In a sealing film that does not have a first intermediate layer 14 and a second intermediate layer 15, it is preferable that the first adhesive layer 11 and / or the second adhesive layer 12 are composed of a specific composition. In one preferred embodiment, at least the second adhesive layer 12 may be composed of a specific composition. In this case, both the first adhesive layer 11 and the second adhesive layer 12 may be composed of a specific composition. Alternatively, the first adhesive layer 11 may be composed of a composition that does not fall under the category of a specific composition, including an acid-modified polyolefin resin.
[0049] If the sealing film comprises a first intermediate layer 14 or a second intermediate layer 15, the second adhesive layer 12 may not be composed of a specific composition, while the first intermediate layer 14 or the second intermediate layer 15 may be composed of a specific composition. Both the first intermediate layer 14 and the second intermediate layer 15 may be composed of a specific composition. The first intermediate layer 14 and / or the second intermediate layer 15 and the second adhesive layer 12 may be composed of a specific composition.
[0050] If the first intermediate layer 14 and / or the second intermediate layer 15 are composed of a specific composition, the first adhesive layer 11 may be composed of a composition that includes an acid-modified polyolefin resin and is not a specific composition. The second adhesive layer 12 may also be composed of a composition that includes an acid-modified polyolefin resin and is not a specific composition. Both the first adhesive layer 11 and the second adhesive layer 12 may also be composed of a composition that includes an acid-modified polyolefin resin and is not a specific composition. If both sides of the sealing film are composed of a composition that is not a specific composition, the composition may be composed of a composition that is less susceptible to thermal degradation than the specific composition. For example, the composition may include the acid-modified crystalline polyolefin resin and not include the polyolefin elastomer.
[0051] In the sealing film of this embodiment, it is more preferable that the specific composition in at least one layer selected from the first or second layer group comprises 35 to 88% by mass of the crystalline polyolefin resin and 12 to 65% by mass of the polyolefin elastomer. With a specific composition having such a composition, it becomes easier to rapidly reduce the sealing strength at high temperatures while providing sufficient sealing strength in the normal operating temperature range.
[0052] In the sealing film of this embodiment, it is preferable that the melting point of the crystalline polyolefin resin contained in the specific composition is 130°C or lower in at least one layer selected from the first or second layer group. Such a crystalline polyolefin resin makes it easier to rapidly reduce the sealing strength at high temperatures. The melting point can be measured as the peak top temperature (melting peak temperature Tpm) of differential scanning calorimetry (DSC measurement) performed in accordance with JIS K7121. If the sealing film comprises two or more layers made of the specific composition, it is preferable that the melting point of the crystalline polyolefin resin is 130°C or lower in at least one layer.
[0053] The sealing film of this embodiment may preferably contain, in at least one layer selected from the first or second layer group, a crystalline polyolefin resin polymerized using a metallocene catalyst as the crystalline polyolefin resin in the specific composition, from the viewpoint of providing sufficient sealing strength in the normal operating temperature range while making it easier to rapidly reduce the sealing strength at high temperatures. Using a metallocene catalyst yields polymers with a low polydispersity index (PDI) and uniform molecular weight. PDI is the ratio of weight-average molecular weight (Mw) to number-average molecular weight (Mn). When the sealing film comprises two or more layers made of the specific composition, it is preferable that at least one layer of the first or second layer group contains a crystalline polyolefin resin polymerized using a metallocene catalyst.
[0054] The crystalline polyolefin resin in the specified composition may be crystalline polyethylene (PE) resin, but crystalline polypropylene (PP) resin is more preferred from the viewpoint of further increasing sealing strength in the normal operating temperature range. The crystalline polyolefin resin may or may not be acid-modified, as described above. The olefin monomer units having 3 or more carbon atoms in the crystalline polyolefin resin include one or more monomer units selected from the group consisting of propylene, butene, hexene, octene, etc. It is preferable that the crystalline polyolefin resin contains propylene monomer units.
[0055] Examples of crystalline PP resins in the aforementioned specific composition include homopolypropylene, random polypropylene, and block polypropylene, each of which may be acid-modified. From the viewpoint of making it easier to rapidly reduce the sealing strength at high temperatures, random polypropylene, which may be acid-modified, is particularly preferred.
[0056] The polyolefin elastomer in the aforementioned specific composition may be a polyethylene (PE) elastomer, but a polypropylene (PP) elastomer is more preferable from the viewpoint of providing sufficient sealing strength in the normal operating temperature range while making it easier to rapidly reduce the sealing strength at high temperatures. A propylene-ethylene-rubber (PER) elastomer is preferred. The olefin monomer units having 3 or more carbon atoms in the polyolefin elastomer include one or more monomer units selected from the group consisting of propylene, butene, hexene, octene, etc. It is preferable that the polyolefin elastomer contains propylene monomer units.
[0057] PE-based elastomers such as ethylene-propylene-rubber (EPR) are polyolefin-based elastomers that contain ethylene monomer units as the main monomer units (for example, more than 50 mol% of the total monomer units, e.g., 60 mol% or more). On the other hand, PP-based elastomers such as PER are polyolefin-based elastomers that contain propylene monomer units as the main monomer units (for example, more than 50 mol% of the total monomer units, e.g., 60 mol% or more), and the two are distinguished from each other. In one embodiment, from the viewpoint of making it easier to rapidly reduce the sealing strength at high temperatures while providing sufficient sealing strength in the normal operating temperature range, it is preferable that the content (in units: mol) of olefin monomer units having 3 or more carbon atoms (e.g., propylene monomer units, etc.) in the total elastomer components contained in the specific composition is greater than the content (in units: mol) of ethylene monomer units, and the ratio of the former to the latter may be, for example, 1.1 mol / mol or more, or 1.5 mol / mol or more.
[0058] In the sealing film of this embodiment, the melt flow rate (MFR) of the polyolefin elastomer contained in the specific composition is not particularly limited. However, from the viewpoint of providing sufficient sealing strength in the normal operating temperature range while making it easier to rapidly reduce the sealing strength at high temperatures, it is preferable that the MFR of the polyolefin elastomer contained in the specific composition in at least one layer selected from the first or second layer group be 4.0 g / 10 min or more, for example, 5.0 g / 10 min or more, or 6.0 g / 10 min or more. If the sealing film comprises two or more layers made of the specific composition, it is preferable that the MFR of the polyolefin elastomer in at least one layer is within the above range. Furthermore, it is more preferable that the MFR of the polyolefin elastomer in at least one layer selected from the layer group be within the above range. The upper limit of the MFR of the polyolefin elastomer is not particularly limited, but it may be, for example, 21 g / 10 min or less. The MFR of the aforementioned polyolefin elastomer is measured under conditions of 230°C and a load of 2.16 kg, in accordance with JIS K7210-1.
[0059] In one embodiment, the core layer 13 may contain one or more polyolefins, each of which may be acid-modified. In the sealing film of this embodiment, from the viewpoint of providing sufficient sealing strength, a heat-resistant resin is preferred for the core layer 13. It is preferable that the heat-resistant resin does not flow easily when heat-sealing using the first adhesive layer 11 and the second adhesive layer 12. More specifically, it is preferable that the core layer 13 contains one or more resins selected from the group consisting of polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyphenylene sulfide (PPS), acid-modified block polypropylene (PP-B), acid-modified homopolypropylene (PP-H), and acid-modified random polypropylene (PP-R) with a melting point of 140°C or higher. The melting point can be measured as the peak top temperature (melting peak temperature Tpm) of differential scanning calorimetry (DSC measurement) performed in accordance with JIS K7121.
[0060] In the sealing film of this embodiment, as described above, the first adhesive layer 11 on the metal terminal side contains an acid-modified polyolefin resin. The acid-modified polyolefin resin may be a known resin, for example, acid-modified polyethylene (PE), but from the viewpoint of increasing the sealing strength in the normal operating temperature range, it is preferable that the first adhesive layer 11 contains acid-modified polypropylene (PP), which has a higher melting point. As the acid-modified polypropylene, acid-modified block polypropylene, acid-modified homopolypropylene, or acid-modified random polypropylene, or any combination thereof can be used, but from the viewpoint of making it easier to increase the fluidity of the resin during heat sealing, it is preferable that the first adhesive layer 11 contains at least acid-modified random polypropylene.
[0061] The melting point of the acid-modified polyolefin resin in the first adhesive layer 11 is preferably 110°C or higher and 150°C or lower, and may be, for example, 120°C or higher, or above 130°C. If the melting point is above the lower limit, the first adhesive layer 11 is less likely to become excessively thin during heat bonding, making it easier to increase the sealing strength. If the melting point is below the upper limit, the resin flows more easily during heat bonding, making it easier to increase the sealing performance between the metal terminal and the sealing film. The acid-modified polyolefin resin contained in the first adhesive layer 11 may be one type or two or more types. If two or more types of acid-modified polyolefin resins are included, it is preferable that the melting point of at least one type is above or above the lower limit, and the melting points of all types may be above or above the lower limit.
[0062] If the sealing film of this embodiment comprises a first intermediate layer 14 and / or a second intermediate layer 15, and at least one of them is composed of a specific composition, the second adhesive layer 12 on the exterior material side may be composed of a composition that does not fall under the category of a specific composition. For example, the first adhesive layer 11 and the second adhesive layer 12 may be composed of the same resin composition. The second adhesive layer 12 may be composed of, for example, a crystalline polyolefin that may be acid-modified.
[0063] As the crystalline polyolefin in the second adhesive layer 12, polyethylene may be used, for example, but from the viewpoint of increasing the sealing strength in the normal operating temperature range, it is preferable that the second adhesive layer 12 contains polypropylene (PP), which has a higher melting point. As the polypropylene, block polypropylene, homopolypropylene, or random polypropylene, or any combination thereof, may be used, each of which may be acid-modified, but from the viewpoint of making it easier to increase the fluidity of the resin during heat-press bonding, it is preferable that the second adhesive layer 12 contains at least acid-modified random polypropylene.
[0064] The melting point of the crystalline polyolefin in the second adhesive layer 12 is preferably 110°C or higher and 150°C or lower, and may be, for example, 120°C or higher, or above 130°C. If the melting point is above the lower limit, the first adhesive layer 11 is less likely to become excessively thin during heat bonding, making it easier to increase the sealing strength. If the melting point is below the upper limit, the resin flows more easily during heat bonding, making it easier to increase the sealing performance between the exterior material and the metal terminal. The crystalline resin contained in the second adhesive layer 12 may be one type or two or more types.
[0065] Each layer constituting the sealing film of this embodiment, namely the first adhesive layer 11, the second adhesive layer 12, the core layer 13, the first intermediate layer 14, and the second intermediate layer 15, may contain various additives for a desired purpose. Examples of such additives are not particularly limited, but include antioxidants, UV absorbers, antistatic agents, lubricants, and anti-blocking agents. One or more of the layers, such as the first adhesive layer 11, the second adhesive layer 12, the core layer 13, the first intermediate layer 14, and the second intermediate layer 15, may have a composition that does not contain one or more of these additives, or all of them.
[0066] The total thickness of the sealing film in this embodiment is not particularly limited, but examples include 10 to 500 μm, 30 to 300 μm, etc.
[0067] The thickness of the first adhesive layer 11 in a sealing film without a first intermediate layer 14 is not particularly limited, but examples include 5 to 200 μm, 10 to 100 μm, etc. The thickness of the first adhesive layer 11 in a sealing film with a first intermediate layer 14 is not particularly limited, but examples include 3 to 100 μm, 5 to 50 μm, etc. The thickness of the first intermediate layer 14 is not particularly limited, but examples include 1 to 100 μm, 3 to 50 μm, etc.
[0068] The thickness of the second adhesive layer 12 in a sealing film without a second intermediate layer 15 is not particularly limited, but examples include 5 to 200 μm, 10 to 100 μm, etc. The thickness of the second adhesive layer 12 in a sealing film with a second intermediate layer 15 is not particularly limited, but examples include 3 to 100 μm, 5 to 50 μm, etc. The thickness of the second intermediate layer 15 is not particularly limited, but examples include 1 to 100 μm, 3 to 50 μm, etc.
[0069] The method for manufacturing the sealing film of this embodiment is not particularly limited, but each layer may be laminated using known methods such as co-extrusion, extrusion lamination, heat lamination, or dry lamination. Adhesives may be used between the layers, or the layers may be laminated without adhesives.
[0070] <Tab leads and batteries> The tab lead of this embodiment comprises a metal terminal and a sealing film of this embodiment that is heat-sealed to the metal terminal, with the first adhesive layer 11 of the sealing film being bonded to the metal terminal. An example of the tab lead of this embodiment is the first composite 111 comprising the test metal terminal 101 (CuNi plate) and the test sealing film 102 described above. However, the tab lead of this embodiment is not limited to this form. For example, as described below, it is also possible to have a tab lead that includes a metal terminal different from the test metal terminal 101 in terms of the type of Ni plating of the CuNi plate, the thickness of the Ni plating, or the thickness of the copper plate portion, the material of the metal terminal, the surface treatment of the metal terminal, the surface roughness of the metal terminal, or the dimensions of the metal terminal, or any combination thereof.
[0071] The dimensions of the metal terminal and sealing film in the tab lead may differ from the dimensions of the test metal terminal 101 (length Lt, width Wt) and the test sealing film 102 (length Lf, width Wf) described above. The sealing film adhered to the metal terminal may be any of the sealing films of this embodiment described above.
[0072] In the tab lead of this embodiment, the material of the metal terminal is not limited to a Ni-plated Cu plate, but can also be CuNi alloy, aluminum (Al), copper (Cu), nickel (Ni), iron (Fe), carbon steel, stainless steel, silver (Ag), gold (Au), iridium (Ir), rhodium (Rh), palladium (Pd), platinum (Pt), or alloys containing at least one of these metals. Furthermore, the metal terminal may have at least a portion of a metal plating layer or a surface treatment layer such as a chemical conversion treatment. Examples of Ni plating include pure Ni plating and nickel-phosphorus (NiP) plating. From the viewpoint of further increasing the adhesive strength with the first adhesive layer 11 containing acid-modified polyolefin, it is preferable that at least the surface of the metal terminal contains a metal element that naturally forms an oxide film in an atmosphere at 25°C and 1 atmosphere. Since such an oxide film reacts with the acid-modified polyolefin, it becomes possible to bring about strong adhesion between the metal terminal and the first adhesive layer 11 by chemical bonding. Examples of such metallic materials include base metal elements such as copper (Cu), aluminum (Al), zinc (Zn), nickel (Ni), iron (Fe), tin (Sn), chromium (Cr), cobalt (Co), indium (In), lead (Pb), tungsten (W), molybdenum (Mo), zirconium (Zr), titanium (Ti), niobium (Nb), vanadium (V), manganese (Mn), gallium (Ga), and bismuth (Bi) (listed in order of decreasing electrical conductivity, with earlier elements being preferred). An alloy containing one or more of these base metal elements may be formed on at least the surface of the metal terminal. These base metal elements may also be present as a plating layer on the surface of the metal terminal. Examples of preferred plating metals include Zn, Ni, Sn, and Cr. The plating may be hot-dip plating, electrolytic plating, or electroless plating. The thickness of the plating layer is not particularly limited, but can be, for example, 0.5 to 15 μm. Furthermore, the metal terminal surface where these metal elements are present may be subjected to additional surface treatments such as chemical conversion treatment.The surface roughness of the metal terminals is not particularly limited; the surface of the metal terminals may be mirror-like (for example, the arithmetic mean height Sa of the surface is less than 0.05 μm), but it may also be, for example, 0.05 to 5 μm for the arithmetic mean height Sa and 0.2 to 25 μm for the maximum height Sz. Alternatively, for example, the metal terminals may have a rougher surface. The definitions of the arithmetic mean height Sa and the maximum height Sz are given in accordance with JIS B0681-2.
[0073] The sides of the metal terminal in the width direction may include cross-sections with shapes that reduce thickness, such as arc-shaped or tapered shapes. For example, the cross-section of the metal terminal may be approximately hexagonal to octagonal. Both ends of the metal terminal in the length direction (first end and second end) are not covered by the sealing film. The first end of the metal terminal can be connected to a power generation element. The second end of the metal terminal can be connected to other components, etc.
[0074] The battery 30 shown in Figure 8 comprises a battery casing 32, a power generation element 31 housed in the battery casing 32, a positive electrode tab lead 20 connected to the positive electrode of the power generation element 31, and a negative electrode tab lead 21 connected to the negative electrode of the power generation element 31. The positive electrode tab lead 20 and the negative electrode tab lead 21 are the tab leads of this embodiment. In these tab leads, the second end of the metal terminal described above is not housed in the casing but is exposed to the outside.
[0075] The illustrated battery casing 32 comprises a main body 33 and a lid 34. A sealing portion 35 is formed on the peripheral edges of the main body 33 and the lid 34 to integrate the battery casing 32. At least one of the main body 33 or the lid 34 may include a concave molded portion 36 for housing the power generation element 31, formed by drawing the battery casing 32. In the illustrated example, the molded portion 36 is formed only on the main body 33, but the molded portion 36 may also be formed on the lid 34.
[0076] The battery casing material 32 is not particularly limited, but it is preferable to include a barrier layer such as metal foil. The barrier layer is not particularly limited, but examples include aluminum foil, stainless steel foil, copper foil, iron foil, etc. The barrier layer may also be a vapor-deposited layer of metal or inorganic oxide (silica, alumina, etc.). Examples of functions of the barrier layer include water vapor barrier and oxygen gas barrier. Furthermore, it is preferable that the battery casing material 32 includes resin layers on the inner and outer surfaces of the barrier layer, respectively.
[0077] Examples of resins laminated on the inner surface of the barrier layer include polyolefin-based sealant resins. Examples of sealant resins include polypropylene-based resins and polyethylene-based resins. Examples of polypropylene-based resins include polypropylene homopolymers and copolymers of propylene and ethylene. Examples of polyethylene-based resins include low-density polyethylene and linear low-density polyethylene. When the sealing film of this embodiment is used as the sealing film for the battery 30, the sealant resin layer of the exterior material and the second adhesive layer 12 of the sealing film may be heat-fused together.
[0078] Examples of resins laminated on the outer surface of the barrier layer include polyamide resins such as aliphatic polyamide (nylon), polyester resins such as polyethylene terephthalate (PET), polyolefin resins such as polypropylene, and phenolic resins. The laminate for exterior materials may have one or more layers of resin substrates, a metal foil, and a sealant resin layer. The layers of two or more resin substrates may be laminated with an adhesive such as a urethane or epoxy adhesive.
[0079] The inside of the battery 30 may contain an electrolyte. Examples of batteries include secondary batteries such as lithium-ion batteries. The electrolyte of the battery may be liquid (electrolyte solution), gel, solid, etc. Examples of electrolytes include various lithium salts. Various carbonate esters may be used as solvents for the electrolyte.
[0080] In the above description of the present invention, a battery 30 in which both the positive electrode tab lead 20 and the negative electrode tab lead 21 are tab leads according to this embodiment was given as an example, but the present invention is not limited to this embodiment. For example, it is also possible to have a battery in which only one of the positive electrode tab lead or the negative electrode tab lead uses a tab lead according to this embodiment. [Examples]
[0081] The present invention will be specifically described below with reference to examples.
[0082] The materials used in each layer of the sealing film are as follows. The ratios are based on mass (mass%), and the unit of MFR is g / 10min. Resins polymerized using a metallocene catalyst are indicated with (m) after PP.
[0083] • "PP1ar": Acid-modified random PP, melting point 140°C. • "PP2ar": Acid-modified random PP, melting point 140°C. • "PP3arm": Acid-modified random PP (m), melting point 125°C. • "PP4ab": Acid-modified block PP, melting point 165°C. • "PP5arm": A mixture containing acid-modified random PP(m), PER, and EPR, with 55% xylene-insoluble content (crystalline component) and 45% xylene-soluble content (rubber component) (20% propylene monomer units, 25% ethylene monomer units), melting point 125°C. • "PP6arm": A mixture containing acid-modified random PP(m), PER, and EPR, with 40% xylene-insoluble content (crystalline component) and 60% xylene-soluble content (rubber component) (35% propylene monomer units, 25% ethylene monomer units), melting point 120°C. • "PP7arm": A mixture containing acid-modified random PP(m), PER, and EPR, with 55% crystalline components and 45% rubber components (25% propylene monomer units, 20% ethylene monomer units), melting point 125°C. • "PP8m": PP(m), melting point 125℃. • "LDPE": Low-density polyethylene (LDPE), MFR = 8.4 (190℃, 2.16kg), melting point 105℃. • "PPTPE1": PP-based elastomer, 100% xylene-soluble content (rubber component) (89% propylene monomer units, 11% ethylene monomer units), MFR = 7 (230℃, 2.16kg). • "PPTPE2": PP-based elastomer, 100% xylene-soluble content (rubber component) (91% propylene monomer units, 9% ethylene monomer units), MFR = 8 (230℃, 2.16kg). • "PETPE": PE-based elastomer, 100% xylene-soluble content (rubber component) (100% ethylene monomer units), MFR=1 (190℃, 2.16kg). • "SEBS": Styrene-ethylene-butadiene-styrene copolymer (SEBS), 45% styrene monomer units, 100% xylene-soluble components (rubber component), MFR=3 (230℃, 2.16kg).
[0084] In the above, the xylene-soluble and xylene-insoluble components are those obtained when the resin is extracted with boiling p-xylene (138°C). For example, a resin sample is completely dissolved in 140 mL of boiling p-xylene per gram of resin, then cooled to 25°C for 8 hours while stirring, and the precipitated components are filtered off as xylene-insoluble components. The xylene-soluble components are obtained from the filtrate. The monomer composition in the xylene-soluble and xylene-insoluble components is as follows: 13 It can be measured by 13C-NMR.
[0085] The proportion of monomer units contained in PPTPE1 and PPTPE2, when converted to mol%, is as follows: PPTPE1: Approximately 85 mol% propylene, approximately 15 mol% ethylene PPTPE2: Approximately 87 mol% propylene, approximately 13 mol% ethylene
[0086] Sealing films were prepared so that each layer had the thickness shown in Tables 1 to 5. The core layer consisted of 75% block PP (melting point 165°C) and 25% PP4ab. The first and second adhesive layers used the resins shown in the corresponding columns of Tables 1 to 5. The first and second intermediate layers used the resins shown in the intermediate layer column of Table 5. In these columns, the components of each composition are indicated by their proportions (mass%) corresponding to the abbreviations representing the materials described above.
[0087] In Table 5, if the thicknesses of the first and second intermediate layers are indicated, the same resin was used for both the first and second intermediate layers. If the thickness of the second intermediate layer is not indicated, that resin was used for the first intermediate layer.
[0088] Following the steps (1) to (4) described above, the peel strengths F23, F80, F110, and F130 were measured. Based on these measurements, the values for F80 / F23, F110 / F23, and F130 / F23 were calculated. The measurement results are shown in Tables 1 to 5.
[0089] The test metal terminal used for measuring peel strength was a CuNi plate, which consisted of a 200 μm thick pure copper plate plated with 2.5 μm thick pure nickel. The surface roughness of the CuNi plate was 0.54 μm as the arithmetic mean height Sa defined in JIS B0681-2, and 12.9 μm as the maximum height Sz defined in JIS B0681-2. Surface roughness was measured using a confocal laser microscope VK-X3000 (manufactured by KEYENCE).
[0090] The test packaging material used to measure peel strength was an aluminum laminate film manufactured by Dai Nippon Printing Co., Ltd. (DNP) (product name D-EL408PH(3), total thickness 153 μm). The specific layer composition (thickness of each layer in parentheses) was polyethylene terephthalate (12 μm) / adhesive (3 μm) / polycaprolactam (15 μm) / adhesive (3 μm) / aluminum (40 μm) / sealant PP (80 μm).
[0091] The DSC chart for the PP sealant used as the test exterior material shows peak top temperatures of 102°C, 138°C, 147°C, and 158°C during the second heating cycle. The heating conditions were 20°C → 200°C (10°C / min, held for 5 minutes after heating) [first heating] → 20°C (10°C / min) [cooling] → 200°C (10°C / min) [second heating].
[0092] [Table 1]
[0093] [Table 2]
[0094] [Table 3]
[0095] [Table 4]
[0096] [Table 5]
[0097] In the sealing films of Examples 1 to 20, F23 was 80 N / 15 mm or higher (I), F80 / F23 was 0.30 or higher (II), F110 / F23 was 0.120 or higher (III), and F130 / F23 was 0.050 or lower (IV). From this, it was confirmed that a sufficiently high level of sealing strength was maintained below the temperature at which it should be opened, and that it was possible to open it quickly when the temperature and internal pressure at which it should be opened were reached.
[0098] The sealing films of Comparative Examples 1-15 and 17 did not satisfy at least (IV). Therefore, it cannot be said that they can be opened quickly when the temperature and internal pressure to be opened are reached.
[0099] The sealing films of Comparative Examples 2-3 and 16-17 did not satisfy at least (I). Therefore, it cannot be said that they can maintain a sufficiently high level of sealing strength below the temperature at which they should be opened.
[0100] Furthermore, the peel strengths measured using the above-mentioned test exterior material and the sealing film of Example 2 were F23=104N / 15mm, F80=62N / 15mm, F110=13N / 15mm, F130=1N / 15mm, F80 / F23=0.60, F110 / F23=0.13, and F130 / F23=0.01. Similar results were obtained when using other exterior materials, such as an aluminum laminate film (total thickness 113μm) with a layer structure of polycaprolactam (25μm) / adhesive (3μm) / aluminum (40μm) / sealant PP (45μm). [Explanation of Symbols]
[0101] Hf…Film heating section, Hm1…First metal heating section, Hm2…Second metal heating section, L…Length direction, Lb…Dimensions of the sealing bar in the length direction, Lf…Length of the test sealing film, Lh…Dimensions of the heat-sealed section in the length direction, Lt…Length of the test metal terminal, T…Thickness direction, W…Width direction, Wf…Width of the test sealing film, Ws…Width of the third composite, Wt…Width of the test metal terminal, 10, 10A, 10B…Sealing film, 11…First adhesive layer, 12…Second adhesive layer 13...core layer, 14...first intermediate layer, 15...second intermediate layer, 20...positive electrode tab lead, 21...negative electrode tab lead, 30...battery, 31...power generation element, 32...battery casing material, 33...main body, 34...lid, 35...sealing part, 36...molded part, 101...test metal terminal, 102...test sealing film, 103...aluminum laminate film, 104...seal bar, 105...heat seal part, 106...cutting line, 111...first composite, 112...second composite, 113...third composite.
Claims
1. A first adhesive layer containing an acid-modified polyolefin resin, The core layer, The second adhesive layer, A sealing film comprising the following in this order: A measurement method comprising the following steps (1), (2), (3), and (4) in this order: (1) Two sealing films, each with a length of 10 mm, are stacked on both sides of a rectangular nickel-plated copper plate (CuNi plate) measuring 40 mm wide x 52.5 mm long with a copper plate portion thickness of 200 μm, such that the ends of the sealing film in the longitudinal direction of the CuNi plate are not covered by the sealing film, the ends of the sealing film in the width direction of the CuNi plate are in contact with each other at the first adhesive layer, and within the width range of the CuNi plate, the first adhesive layer is in contact with the CuNi plate, in the order of sealing film-CuNi plate-sealing film, and in the longitudinal direction, the two sealing films are in contact with the CuNi plate facing each other. A heat sealing machine comprising, in this order, a pair of first metal heating units, a pair of film heating units facing the sealing film and in contact with each other via polytetrafluoroethylene tape, and a pair of second metal heating units facing the CuNi plate and in contact, is used to perform heat sealing for 25 seconds while applying pressure at 0.2 MPa under conditions where the temperatures of the first and second metal heating units are 180°C and the temperature of the film heating units is 150°C, thereby bonding the sealing film to the CuNi plate and obtaining a first composite having a layer structure of sealing film-CuNi plate-sealing film. (2) A step to obtain a second composite having a layer structure of aluminum laminate film having a polyethylene terephthalate layer / polycaprolactam layer / aluminum foil / polypropylene layer with a melting point of 140°C, which is superimposed on the sealing film portions on both sides of the first composite such that the polypropylene layer is in contact with the second adhesive layer of the sealing film, and a heat seal is performed at 190°C for 3.5 seconds using a seal bar with a heat seal width of 4.5 mm along the length direction, thereby obtaining a second composite having a layer structure of aluminum laminate film - sealing film - CuNi plate - sealing film - aluminum laminate film. (3) The second composite is cut in a direction that crosses the sealing film in the width direction, and a third composite with a width of 15 mm is cut out. (4) The CuNi plate of the third composite is fixed, and a 180° peel test is performed on one of the aluminum laminate films at a temperature of 23°C, 80°C, 110°C, or 130°C and a tensile speed of 50 mm / min, and the peel strength is measured. The peel strength measured by the method is expressed in the following relationship (I), (II), (III), and (IV), where F23 is the peel strength at 23°C in step (4), F80 is the peel strength at 80°C in step (4), F110 is the peel strength at 110°C in step (4), and F130 is the peel strength at 130°C in step (4): F23≧80N / 15mm...(I) F80≧0.30×F23...(II) F110≧0.120×F23...(III) F130≦0.050×F23...(IV) A sealing film that satisfies the requirements.
2. Each layer in the group of layers, which includes at least one layer other than the core layer, A crystalline polyolefin resin containing olefin monomer units having 3 or more carbon atoms, which may be acid-modified, A polyolefin-based elastomer containing more than 50 mol% of olefin monomer units having 3 or more carbon atoms and more than 0 mol% but less than 50 mol% of ethylene monomer units, The sealing film according to claim 1, including the following:
3. The sealing film according to claim 2, wherein the melting point of the crystalline polyolefin resin contained in each layer of the layer group is 130°C or lower.
4. Each layer of the aforementioned group of layers The crystalline polyolefin resin is present in an amount of 35 to 88% by mass, The aforementioned polyolefin elastomer is present in an amount of 12 to 65% by mass, The sealing film according to claim 2, including the following:
5. The second adhesive layer, A crystalline polyolefin resin containing olefin monomer units having 3 or more carbon atoms, which may be acid-modified, A polyolefin-based elastomer containing more than 50 mol% of olefin monomer units having 3 or more carbon atoms and more than 0 mol% but less than 50 mol% of ethylene monomer units, The sealing film according to claim 1, including the following:
6. The sealing film according to claim 5, wherein the melting point of the crystalline polyolefin resin contained in the second adhesive layer is 130°C or lower.
7. The second adhesive layer, The crystalline polyolefin resin is present in an amount of 35 to 88% by mass, The aforementioned polyolefin elastomer is present in an amount of 12 to 65% by mass, The sealing film according to claim 5, including the following:
8. The present invention further comprises a first intermediate layer disposed between the first adhesive layer and the core layer, The first intermediate layer is A crystalline polyolefin resin containing olefin monomer units having 3 or more carbon atoms, which may be acid-modified, A polyolefin-based elastomer containing more than 50 mol% of olefin monomer units having 3 or more carbon atoms and more than 0 mol% but less than 50 mol% of ethylene monomer units, The sealing film according to claim 1, including the following:
9. The sealing film according to claim 8, wherein the melting point of the crystalline polyolefin resin contained in the first intermediate layer is 130°C or lower.
10. The first intermediate layer is The crystalline polyolefin resin is present in an amount of 35 to 88% by mass, The aforementioned polyolefin elastomer is present in an amount of 12 to 65% by mass, The sealing film according to claim 8, including the following:
11. The present invention further comprises a second intermediate layer disposed between the second adhesive layer and the core layer, The second intermediate layer is A crystalline polyolefin resin containing olefin monomer units having 3 or more carbon atoms, which may be acid-modified, A polyolefin-based elastomer containing more than 50 mol% of olefin monomer units having 3 or more carbon atoms and more than 0 mol% but less than 50 mol% of ethylene monomer units, The sealing film according to claim 1, including the following:
12. The sealing film according to claim 11, wherein the melting point of the crystalline polyolefin resin contained in the second intermediate layer is 130°C or lower.
13. The second intermediate layer is The crystalline polyolefin resin is present in an amount of 35 to 88% by mass, The aforementioned polyolefin elastomer is present in an amount of 12 to 65% by mass, The sealing film according to claim 11, including the following:
14. The sealing film according to claim 2, wherein the crystalline polyolefin resin is a crystalline polyolefin resin polymerized using a metallocene catalyst.
15. The sealing film according to claim 1, wherein the core layer comprises one or more resins selected from the group consisting of polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyphenylene sulfide (PPS), optionally acid-modified block polypropylene (PP-B), optionally acid-modified homopolypropylene (PP-H), and optionally acid-modified random polypropylene (PP-R) with a melting point of 140°C or higher.
16. Metal terminals and A sealing film according to any one of claims 1 to 15, which is adhered to the metal terminal, A tab lead equipped with a tab lead.
17. Battery casing material, The power generation element housed in the aforementioned battery casing, A positive electrode tab lead connected to the positive electrode of the power generation element, The system comprises a negative electrode tab lead connected to the negative electrode of the power generation element, A battery in which at least one of the positive electrode tab lead and the negative electrode tab lead is the tab lead described in claim 16.
Citation Information
Patent Citations
Resin film for terminal and power storage device using the same
JP2022165772A
Tab sealant and power storage device using the same
JP2023006252A
Adhesive film for metal terminal, method for manufacturing adhesive film for metal terminal, metal terminal with adhesive film for metal terminal, electricity storage device, and method for manufacturing electricity storage device
JP7088437B2